2019
DOI: 10.3390/f10020100
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis and Expression Profiling of the Heat Shock Factor Gene Family in Phyllostachys edulis during Development and in Response to Abiotic Stresses

Abstract: Heat shock transcription factors (Hsfs) play crucial roles in regulating plant responses to heat and other stresses, as well as in plant development. As the largest monopodial bamboo species in the world, how to adapt to various stresses under the background of global climate change is very important for the sustainable development of bamboo forest. However, our understanding of the function of Hsfs in moso bamboo (Phyllostachys edulis) is limited. In this study, a total of 22 non-redundant Hsf genes were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 65 publications
2
10
0
Order By: Relevance
“…DcaHsf-A2a, A2b revealed to be strongly induced under heat stress conditions. This indicates that HsfA2 is a dominant regulator during the heat stress response in carnation, which is consistent with the studies of Arabidopsis , tomato, apple, Populus euphratica , and Phyllostachys edulis [11,22,38,39,45]. HsfA3 has been identified as an important player in the responses to heat, high salinity, and drought stresses in Solanum lycopersicum [46], whereas a similar function for HsfA3 is not detected in tomato [14].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…DcaHsf-A2a, A2b revealed to be strongly induced under heat stress conditions. This indicates that HsfA2 is a dominant regulator during the heat stress response in carnation, which is consistent with the studies of Arabidopsis , tomato, apple, Populus euphratica , and Phyllostachys edulis [11,22,38,39,45]. HsfA3 has been identified as an important player in the responses to heat, high salinity, and drought stresses in Solanum lycopersicum [46], whereas a similar function for HsfA3 is not detected in tomato [14].…”
Section: Discussionsupporting
confidence: 83%
“…In our study, DcaHsf-A1 demonstrated up-regulation in S, CA, YL, and ML (Figure 5). Phyllostachys edulis PheHsfA2a-2 is predicted to play an important role in flower and shoot development [38] and Cicer arietinum CarHsfA2 is up-regulated in shoot, root, and flower [12]. Their orthologs in carnations, DcaHsf-A2a, A2b , were constitutively expressed in S, CA, YL, and ML at relatively high levels (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…With the publishing of the moso bamboo genome [27] and the bamboo genome database (BambooGDB) [28], the work on gene identification at the whole-genome level is being greatly accelerated. Genome-wide analysis of IQD [29], SBP-like [30], TCP [31], heat shock [32], and MYB [33] has been performed in moso bamboo. Although identification and function analysis of HB genes have been widely carried out in many plant species such as rice, grapes, and carrots [34][35][36], a comprehensive understanding of the status of HB genes is lacking in moso bamboo, and those associated with lignification are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Bamboo forests are an important type of forest in tropical and subtropical areas, covering a total area of 31.5 million ha in 2010 and accounting for approximately 0.8% of the world's total forest area [1]. Moso bamboo (Phyllostachys edulis (Carrière) J. Houzeau, synonym Phyllostachys heterocycla (Carrière) is currently the most important source of woody bamboo [2]. The shoot of moso bamboo can grow from 0-20 m in 45-60 days under suitable spring conditions [3].…”
Section: Introductionmentioning
confidence: 99%